1984
DOI: 10.1093/nar/12.17.6663
|View full text |Cite
|
Sign up to set email alerts
|

Codon usage can affect efficiency of translation of genes inEscherichia coli

Abstract: By inserting synthetic oligonucleotides into a highly expressed gene in E. coli it has been shown that unfavourable codon usage can reduce the maximum translation rate of a protein. However, in the case of the codon used (AGG), a significant effect on translation was only seen at very high transcription rates from a gene containing multiple copies of the unfavourable codon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
157
1
3

Year Published

1985
1985
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 295 publications
(166 citation statements)
references
References 25 publications
5
157
1
3
Order By: Relevance
“…Consequently, we cannot exclude that codon usage could also improve the rate of elongation of protein synthesis. Moreover, several experiments conducted on E. coli show that optimal codons could increase both the accuracy and the speed of translation (Robinson et al 1984;Precup and Parker 1987;Sorensen et al 1989). Thus codon usage is possibly related to both the elongation rate and the accuracy of translation.…”
Section: Does Codon Usage Improve the Accuracy The Speed Of Translatmentioning
confidence: 99%
“…Consequently, we cannot exclude that codon usage could also improve the rate of elongation of protein synthesis. Moreover, several experiments conducted on E. coli show that optimal codons could increase both the accuracy and the speed of translation (Robinson et al 1984;Precup and Parker 1987;Sorensen et al 1989). Thus codon usage is possibly related to both the elongation rate and the accuracy of translation.…”
Section: Does Codon Usage Improve the Accuracy The Speed Of Translatmentioning
confidence: 99%
“…However, we propose that these two slowly translated codons are avoided by slow regions (that occur at mRNA spans that correspond to the strategic positions on proteins such as domain ends) because they may induce dissociation of the translation complex and cause a deleterious rather an intentional pause. Many reports in the literature (Robinson et al, 1984;Bonekamp et al, 1985;Spanjaard & van Duin, 1988;Varenne et al, 1989, Chen & Inouye, 1990Spanjaard et al, 1990;Kinnaird et al, 1991;Rosenberg et al, 1993;Goldman et al, 1995) show that the introduction of cua (Leu) or agg (Arg) codon strings results in the reduction of protein yield and presumably induces dissociation of the translation complex or frameshifting and hopping (Kane et al, 1992) events. Chen and Inouye (1990) observed preferential use of such codons in the region spanning the first 25 codons of the mRNA; they suggest that such a preference for the minor codons in an early gene section may modulate gene expression by premature termination of translation, thereby avoiding unnecessary translation of a large part of the mRNA.…”
Section: Rare Codons and Their Usage In Slow Regionsmentioning
confidence: 99%
“…However, the presence of the rare codon AGA (codon 402 of the coding region) is the most likely reason for the temporary accumulation of the 46000-M, polypeptide. The significance of rare codons in regulatory and minor proteins has been studied before [15-201, and recently [21] it has been shown that the insertion in tandem of four of the extremely rare codon (Arg AGG) into the E. coli cut gene significantly reduces the level of expression. For some E. coli proteins the synonymous codons are used in a non-random manner and the codons preferred are those recognised by the most abundant tRNA species in the cell; the concentration of each tRNA and the frequency of usage of the synonymous codons have been listed by Ikamura [22,231.…”
Section: Discussionmentioning
confidence: 99%